The Human Papillomavirus (HPV) E6 Oncoprotein Regulates CD40 Expression via the AT-Hook Transcription Factor AKNA - Manzo-Merino, Joaquin (Cancers (Basel), 2018)
Persistent infection with high-risk Human Papillomavirus (HR-HPV) is the main requisite for cervical cancer development. Normally, HPV is limited to the site of infection and regulates a plethora of cellular elements to avoid the immune surveillance by inducing an anti-inflammatory state, allowing the progress through the viral cycle and the carcinogenic process. Recent findings suggest that the AT-hook transcriptional factor AKNA could play a role in the development of cervical cancer. AKNA is strongly related to the expression of co-stimulatory molecules such CD40/CD40L to achieve an anti-tumoral immune response. To date, there is no evidence demonstrating the effect of the HPV E6 oncoprotein on the AT-hook factor AKNA. In this work, minimal expression of AKNA in cervical carcinoma compared to normal tissue was found. We show the ability of E6 from high-risk HPVs 16 and 18 to interact with and down-regulate AKNA as well as its co-stimulatory molecule CD40 in a proteasome dependent manner. We also found that p53 interacts with AKNA and promotes AKNA expression. Our results indicate that the de-regulation of CD40 and AKNA is induced by the HPV E6 oncoprotein, and this event involves the action of p53 suggesting that the axis E6/p53A/AKNA might play an important role in the de-regulation of the immune system during the carcinogenic process induced by HR-HPV.